Willis covered stent treatment for blood blister-like aneurysm: A meta-analysis of efficacy and safety - Tan, Jiahe; Song, Rui; Luo, Siyue; Fu, Wenqiao; Su, Jun; He, Zhaohui (Frontiers in Neurology, 2023)
Background: Blood blister-like aneurysm (BBA) is a rare and special type of intracranial aneurysms with extremely high rates of rupture, morbidity, mortality, and recurrence. Willis Covered Stent (WCS) is a new device specifically designed for the treatment of intracranial complex aneurysms. However, the efficacy and safety of WCS treatment for BBA remains controversial. Thus, a high level of evidence is required. Methods: Systematic literature review was performed in Medline, Embase, and Web of Science databases to identify studies related to WCS treatment for BBA. A meta-analysis was then conducted to incorporate the outcomes of efficacy and safety, including intraoperative situation, postoperative situation, and follow-up data. Results: Eight noncomparative studies containing 104 patients with 106 BBAs met the inclusion criteria. In intraoperative situation, the technical success rate was 99.5% (95% confidence interval (CI), 0.958, 1.000), the complete occlusion rate was 98.2% (95% CI, 0.925, 1.000), and the side branch occlusion rate was 4.1% (95% CI, 0.001, 0.114). Vasospasm and dissection occurred in 9.2% (95% CI, 0.000, 0.261) and 0.1% (95% CI, 0.000, 0.032) of the patients, respectively. In postoperative situation, the rebleed and mortality rates were 2.2% (95% CI, 0.000, 0.074) and 1.5% (95% CI, 0.000, 0.062), respectively. In follow-up data, recurrence and parent artery stenosis occurred in 0.3% (95% CI, 0.000, 0.042) and 9.1% (95% CI, 0.032, 0.168) of the patients, respectively. Ultimately, 95.7% (95% CI, 0.889, 0.997) of the patients had a good outcome. Conclusions: WCS could be effectively and safely applied for BBA treatment. The results provide a reference for clinical trials in the future. Well-designed prospective cohort studies must be conducted for verification.